Interdisciplinarity in the law in Mexico: an analysis of “The decline of law as an autonomous discipline: 1962-1987” by Richard Posner, and its application to the Mexican case - Sherling-Campos, Eduardo Isaías (Universidad Autónoma de Tamaulipas, 2010)
Taking a look at the curricula of law faculties of universities in Mexico, we found several chairs that have a particular relationship to the study of law from “another perspective.” Where does this law phenomenon come from? To try to answer this question It is drawing some arguments of a famous article in the American academic Richard Posner, applying to the Mexican case the decay of the accused in the law as an autonomous discipline in the United States